Radiation-induced bystander effect and its clinical implications - Tang, Haoyi; Cai, Luwei; He, Xiangyang; Niu, Zihe; Huang, Haitong; Hu, Wentao; Bian, Huahui; Huang, Hao (Frontiers in Oncology, 2023)
For many years, targeted DNA damage caused by radiation has been considered the main cause of various biological effects. Based on this paradigm, any small amount of radiation appears to be harmful to the organism. With the epidemiological study on Japanese atomic bomb survivors, the linear-non-threshold model (LNT) has become the dominant standard in the field of radiation protection. However, there is increasing evidence that the LNT model is not fully applicable to the biological effects caused by low dose radiation, and theories related to low dose radiation need to be further understood. Beyond the cell damage induced by direct exposure, non-targeted effects, usually referred to as bystander effects, abscopal effect, genetic instability, etc., are another kind of significant effect in the realm of low dose radiation. A deep understanding of this phenomenon is crucial for both basic medical research and clinical therapy. This article reviews the latest literature on the bystander effect and summarizes the key findings in this field. Additionally, it offers a cross-sectional comparison of bystander effects caused by various radiation sources in different cell types, as well as an in-depth analysis of studies on the potential biological mechanisms of bystander effects. This review aimed to delineate knowledge about the bystander effect to enlighten both radiobiologists and clinical radiologists in the search for new ways of improving clinical treatment.